Rydberg antiblockade regimes: Dynamics and applications. (17th September 2020) - Su, S.-L.; Guo, F.-Q.; Wu, J.-L.; Jin, Z.; Shao, X. Q.; Zhang, S.
Abstract: Rydberg antiblockade (RAB) allows more than one Rydberg atom to be excited in the presence of Rydberg-Rydberg interaction (RRI) and has many potential applications in quantum optics, many-body physics and quantum information. In this paper, we would review the conditions and possible applications of different types of RAB regimes under weak, intermediate and strong RRIs, respectively. Both van der Waals (vdW) and dipole-dipole (DD) interactions are considered for each interaction strength. This work displays the layout of RAB and provides a reference for further study of RAB-regime-based quantum optics and quantum information processing tasks.